The hydrological impact of the mediterranean forest: a review of French research - Cosandey, Claude; Andréassian, Vazken; Martin, Claude; Didon-Lescot, Jean-François; Lavabre, Jacques; Folton, Nathalie; Mathys, Nicolle; Richard, Didier (Journal of hydrology (Amsterdam), 2005)
Forest hydrology studies carried out in France have focused mainly on the Mediterranean part of the country. Three experimental catchments groups exist and have been monitored over a long period. Some forested catchment (Draix catchment) underwent no change during the study period, while others experienced either clear cutting (Lozère catchment) or forest fires (part of the Réal Collobrier catchments). In each case studied, the behaviour of the forested catchment was compared to that of a control catchment. Included with the experimental catchments studies are the results of research with a fundamentally different approach. The research is based on a statistical study of the interrelated development of afforestation rates and runoff characteristics for average-sized catchments (around 100 km2) in that part of the southern French Massif Central which is subject to Mediterranean rainfall conditions. The results differ considerably from one site to another, indicating the degree of complexity of the rainfall/discharge relationship. An increase in extreme flood events due to forest disturbance could by no means be confirmed in every case. A closer look at the hydrological behaviour of the catchments cleared up the apparent inconsistencies. It is mainly the contrast between bare soil and vegetated soil, rather than between forest and other types of vegetation witch is relevant in explaining the hydrological behaviour.